2008
DOI: 10.1055/s-0028-1083512
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Ammonium-Tagged Olefin-Metathesis Catalyst for Simplified Purification

Abstract: When an 2-isopropoxy-substituted benzylidene ligand of a Hoveyda-type Ru-metathesis complex is modified by an additional 4-diethylamino group and treated wit PTSA it yields a highly active precatalyst suitable for RCM, cross metathesis, and enyne metathesis. The important property of this ammonium tagged Rucomplex is associated with the possibility of its easy removal by a simple filtration protocol.During recent years, olefin metathesis using modern ruthenium catalysts has become a key reaction in organic che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…[23] However, under acidic conditions, a faster conversion rate was observed with the precatalyst 2 c, which led in situ to an activated benzylidene ether based catalyst by means of the electron-donating to electronwithdrawing switch through the protonation of the basic dimethylamine function. [24] It is important to note that this type of acid-mediated metathesis catalytic activation has only recently been described with a ruthenium complex that bore two nonidentical NHC ligands, in which one is a mesoionic carbene (MIC) that possesses an unsubstituted nitrogen atom prone to react with a molecule of acid. [22b, 25] In the present example, the strong potential for protonolysis could be attributed to the more basic cycloalkylamine moiety.…”
Section: Resultsmentioning
confidence: 99%
“…[23] However, under acidic conditions, a faster conversion rate was observed with the precatalyst 2 c, which led in situ to an activated benzylidene ether based catalyst by means of the electron-donating to electronwithdrawing switch through the protonation of the basic dimethylamine function. [24] It is important to note that this type of acid-mediated metathesis catalytic activation has only recently been described with a ruthenium complex that bore two nonidentical NHC ligands, in which one is a mesoionic carbene (MIC) that possesses an unsubstituted nitrogen atom prone to react with a molecule of acid. [22b, 25] In the present example, the strong potential for protonolysis could be attributed to the more basic cycloalkylamine moiety.…”
Section: Resultsmentioning
confidence: 99%
“…1). 12,13,14 It was shown that simple filtration of the reaction mixture through silica gel results in lowering the amount of catalyst impurities in the crude products, however in the most cases the residual Ru level was still too high for pharmaceutical applications. 12 This problem is probably related to placing of the quaternary ammonium group in the benzylidene part which dissociates during metathesis act.…”
mentioning
confidence: 99%
“…To date, 1 has been scarcely used in olefin cross metathesis transformations. In some examples, Grela used 1 as a test substrate to evaluate the efficiency of new catalysts [ 26 ], and Cossy prepared vinyl functionalized oxazoles [ 27 ]. To our knowledge, the cross metathesis of 1 with electron-deficient olefins has not been reported.…”
Section: Resultsmentioning
confidence: 99%